FIGURE 29. A–F in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 29. A–F, Portunus anceps (Saussure, 1857). A, B, Female, cl 10.6 mm, cw 21.9 mm (MZUSP 40178). C, Male, cl 8.9 mm, cw 17 mm (MZUSP 33826). D, Juvenile, cl 2.9 mm, cw 3.9 mm (MZUSP 40185). Note in (C, D) changes with growth in the shape of the carapace and development of the submedian frontal teeth (arrows); the submedian frontal teeth more advanced in the younger stage (D). E, F, Male, cl 6.5 mm, cw 12 mm (MZUSP 40184). Habitus, dorsal (A, C–E) and ventral (B, F). Photographs by A. Pol. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 57, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155